20 MAGNETIC RESONANCE SPECTROSCOPY AND IMAGING OF TERM NEONATES AFTER HYPOXIC ISCHEMIC ENCEPHALOPATHY FOR PREDICTING LONG-TERM OUTCOME. (1st January 2005) - Carr, C.; Ashwal, S.; Wycliffe, D.; Michelson, D.; Holshouser, B.
Abstract : Hypoxic ischemic encephalopathy (HIE) is a significant cause of morbidity and mortality in neonates. In recent years, magnetic resonance imaging (MRI) and proton magnetic resonance spectroscopy (MRS) have been shown to be useful in predicting neurologic outcome for a variety of CNS injuries in all pediatric age groups. The objective of this study was to determine 1) if early measurements of MRS metabolites such as N-acetylaspartate (NAA), creatine (Cr), choline (Cho), myo-Inositol (Ins), glutamate/glutamine (Glx) and lactate (Lac) can predict long-term (6-12 mo) neurologic outcome in neonates with HIE and 2) if abnormalities seen on MRI correlate with MRS findings. In this retrospective study, we included 21 term neonates with confirmed HIE in whom MRI and MRS was obtained within the first two weeks of life (mean 8 ± 4 days). Metabolite ratios were determined for occipital gray matter (OGM), basal ganglia (BG) and thalami (TH). MR images were scored for basal ganglia and watershed region injury by a neuroradiologist using a validated MR scoring system. Neurologic outcome was determined 6-12 months after injury by a pediatric neurologist and dichotomized into good (normal, mild disabilities) and poor (moderate and severe disabilities, vegetative state or dead) outcomes. We found that patients with poor outcomes (n=6) had significantly decreased NAA/Cr (p= 0.02), NAA/Cho (p = 0.001) and Ins/Cr (p=.05) and increased Cho/Cr (p = 0.001) ratios compared to the good outcome group (n= 15) in OGM. In addition, lactate was found in 83% of patients with poor outcomes vs 13% with good outcomes (p=.002). In the BG, we found that patients with poor outcomes (n = 5) had decreased NAA/Cho (p = 0.05) and increased Cho/Cr (p = 0.04) and decreased NAA/Cre (p=.04) in the TH. Strong and significant correlations were found between NAA/Cho and Cho/Cre ratios from OGM and BG with MRI scores from BG. A logistic regression model using two variables, NAA/Cho from OGM and the MRI score from the basal ganglia, was able to predict dichotomized outcome with 95% accuracy with one false negative prediction. Early MRS in combination with MRI was found to be useful for predicting long-term outcome after HIE in neonates.